Integrating network pharmacology and molecular modeling to decipher the anti-esophageal squamous cell carcinoma mechanisms of Bidens pilosa L - Zhenzhen Yang; Cheng Chang; Na Gao; Pan Gao; Yinsen Song; Ruiting Feng; Jingjie Meng; Chen Wang; Haozhe Zhang; Tianli Fan (Discover Oncology)
Abstract Bidens pilosa L (BL), known for its anti-inflammatory, antioxidant, and anticancer properties across multiple malignancies, was investigated for its potential therapeutic effects against esophageal squamous cell carcinoma (ESCC). Through integrative network pharmacology and computational approaches, 10 bioactive compounds from BL were identified from HERB 2.0, symMap, BATMAN-TCM (target prediction score cutoff = 20, adjusted P-value = 0.05 for target analyses), TCMSP (oral bioavailability ≥ 30% and drug likeness ≥ 0.18), and ETCM 2.0 databases, while 3,993 ESCC-associated targets were retrieved from OMIM, GeneCards, and DisGeNET. Cross-analysis revealed 214 shared targets, with tyrosine-protein kinase, epidermal growth factor receptor, and alpha serine/threonine-protein kinase emerging as central hubs in protein-protein interaction networks. Functional enrichment analysis highlighted significant involvement in cellular responses to hormone stimuli, nitrogen compounds, and phosphorylation, with key pathways including cancer, PI3K-Akt, and Ras signaling. Molecular docking demonstrated high-affinity binding of (2E)-2-(3,4-Dihydroxybenzylidene)-6,7-Dihydroxy-Benzofuran-3-One (− 10.4 kcal/mol), Luteolin (− 10.1 kcal/mol), and Okanin (− 9.7 kcal/mol) to matrix metalloproteinase-9 (MMP9), specifically targeting catalytic residues GLU227 and TYR245. Quantum chemical calculations further revealed narrow HOMO-LUMO gaps for Luteolin (ΔE = 2.41 eV) and Okanin (ΔE = 2.93 eV), indicating high reactivity, while molecular dynamics simulations confirmed stable MMP9-ligand complexes (nearly − 200 kJ/mol), with Okanin exhibiting faster equilibration than Luteolin. The analysis of datasets from TCGA and GEO revealed that MMP9 is significantly upregulated in esophageal squamous cell carcinoma tissues compared to normal esophageal tissues. Meanwhile, Luteolin significantly inhibited the proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) capabilities of ESCC in vitro experiments.These findings collectively suggest that BL exerts anti-ESCC effects in silico through multi-target synergy, with Luteolin and Okanin identified as promising MMP9 inhibitors, providing a mechanistic foundation for future drug development.